An Ultra-Compact X-ray Regenerative Amplifier Free-Electron Laser - Madison Singleton; James Rosenzweig; Jingyi Tang; Zhirong Huang (Instruments, 2024)
There is a growing interest in designing and building compact X-ray Free Electron Lasers (FELs) for scientific and industry applications. In this paper, we report an X-ray Regenerative Amplifier FEL (XRAFEL) design based on a proposed Ultra Compact X-ray FEL configuration. Our results show that an XRAFEL can dramatically enhance the temporal coherence and increase the spectral brightness of the radiation in the hard X-ray regime without increasing the footprint of the FEL configuration. The proposed compact, fully coherent, and high-flux hard X-ray source holds promise as a valuable candidate for a wide range of high-impact applications in both academia and industry.